The Analysis of Slope Stability using The Simplified Bishop Method and Geometry of Retaining Walls in Palaran District, Samarinda City, East Kalimantan Province - Akbar Ilham; Tommy Trides; Harjuni Hasan; Revia Oktaviani; Albertus Juvensius Pontus (Nusantara Civil Engineering Journal, 2023)
Landslide is one of the natural disasters that often occurs on natural and artificial slopes. This landslide occurs due to an imbalance of forces acting on the slope or the actuator in the slope area is greater than the resisting force on the slope. Handling needs to be done to avoid landslides, one of which is making a retaining wall. Based on the data obtained from the results of the tests and calculations that have been carried out, the value of the slope safety factor at the research location is 0.397. This value is the value of the unsafe factor of safety (Avalanche). So it is necessary to design a retaining wall with dimensions in between, namely for H = 7 m, H1 = 0.7 m, H2 = 6.3 m, H3 = 1.6 m, H4 = 0.7 m, H5 = 4.9 m, H6 = 2.6 m, H7 = 0.5 m, H8 = 2.5 m, H9 = 3.8 m, and D = 2.5 m. And the results of calculating the stability of the retaining wall that has been designed are obtained for Stability Against Overturning, namely 4.37 > 1.5 (Safe), Stability Against Shifting, namely 2.21 > 2 (Safe), and Stability Against Soil Bearing Capacity, namely 4.14 > 3 (Safe).